(untitled) (Revista Apotheke, 2019)
This paper addresses the design on the sand surface observed in aesthetic journeys made in Pontal da Daniela locatedin Florianopolis, Santa Catarina. In artistic practices by the edge of the beach, there was photographic images of small species of trails, inhabitants of this place that made up natural and spontaneous drawings without human interference. In the process of writing, between philosophical and poetic articulations, these images are presented in intersections with the notions of invisibility and visibility, present in the drawing language in Jacques Derrida, and with the configuration of an almost virtuality in David Lapoujade’s views. Finally, the configuration of the work proposes to bring the sketches that are drawn and inscribed in the sandy territory, intensifying their minimum existences.